Quarantine pathogen interceptions on crop germplasm in India during 1986 - 2010 and their possible economic impact - R D V J PRASADA RAO; K ANITHA; S K CHAKRABARTY; A G GIRISH; B SARATH BABU; K RAMEASH; BABU ABRAHAM; K S VARAPRASAD (The Indian Journal of Agricultural Sciences, 2024)
The National Bureau of Plant Genetic Resources Regional Station, Hyderabad has facilitated safe introduction of 356 521 (1986–2010) germplasm accessions of various crops into India. About 60 seed-borne pathogens of quarantine importance were intercepted on crop germplasm during seed examination in the laboratory and post-entry quarantine observations in the field. Of these, the quarantine pathogens, viz. Ralstonia solanacearum and peanut stripe virus in groundnut (Arachis hypogaea L.), Peronospora manshurica (Naum.) Syd. and peanut stripe virus in soybean [Glycine max (L.) Merr.], tobacco streak virus in sunflower (Helianthus annuus L.), Xanthomonas campestris pv holcicola (Elliot) Dye, Burkholderia andropogonis (Smith) Gillis et al. on sorghum [Sorghum bicolor (L.) Moench], Drechslera maydis (Nisik.) Subram. & Jain on maize (Zea mays L.) and Pseudomonas syringae pv tomato (Okabe) Young et al. on tomato (Lycopersicon esculentum Mill.) were intercepted from different countries. Yield losses that could have occurred were estimated had these pathogens of groundnut, soybean, sunflower, maize, sorghum and tomato not been intercepted.